2004
DOI: 10.1001/archpsyc.61.11.1146
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Serotonin Transporter Gene Variation and RearingCondition in Alcohol Preference and Consumption in Female Primates

Abstract: These data suggest a potential interaction between serotonin transporter gene variation and early experience in vulnerability to alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
181
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 239 publications
(192 citation statements)
references
References 50 publications
9
181
2
Order By: Relevance
“…Furthermore, the leptin data indicate that s-variant females are more responsive to the adverse effects of group formation than l/l females who become subordinate. Although we saw no genotype differences in glucocorticoid negative feedback, we hypothesize that these effects of SERT genotype are due to differences in reactivity to the social environment [20,74], perhaps the result of a disruption in 5HT regulation of central CRH circuits conferred by the short allele variant.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, the leptin data indicate that s-variant females are more responsive to the adverse effects of group formation than l/l females who become subordinate. Although we saw no genotype differences in glucocorticoid negative feedback, we hypothesize that these effects of SERT genotype are due to differences in reactivity to the social environment [20,74], perhaps the result of a disruption in 5HT regulation of central CRH circuits conferred by the short allele variant.…”
Section: Discussionmentioning
confidence: 55%
“…153 Evidence from animal studies also supports the 5-HTTLPR G Â E in the genesis of alcohol dependence. 8,154 On the other hand, there appears to be some degree of specificity as no G Â E was identified for generalised anxiety disorder or anxiety symptoms. 15,34 While 5-HTTLPR genotype is not reliably directly associated with depression, 151 the more severe and multiple adverse outcomes including violent suicide, 155,156 suicide attempts among alcohol-dependent subjects 157 and comorbid alcohol dependence with depression 158,159 are directly associated with 5-HTTLPR s allele loading.…”
Section: Genetic Control Of the Environmentmentioning
confidence: 99%
“…9 The less active s-allele interacts with adverse early rearing conditions (peer rearing) to result in more distress, less activity, stronger neuroendocrine responses to stress, higher consumption of alcohol and lower serotonin turnover in the central nervous system. 8,9,26,27 During peerrearing, animals homozygous for the l allele develop more socially acceptable playful behaviours but sl heterozygotes tend to become aggressive, suggesting that the ll homozygous status confers an adaptive potential for adverse environment. 28 In conclusion, the non-human primate experiments support the G Â E hypothesis by showing that the s allele is associated with a vulnerability to early life adverse circumstances leading to multiple adverse outcomes resembling human psychiatric disorders.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Moreover, a gene  environment interaction between 5-HTTLPR and stressful life events in the development of mood disorder and suicide attempts was observed, 27 and a gene  environment interaction for an orthologous serotonin transporter polymorphism in the Rhesus macaque was also noted. 28 Recent studies [29][30][31] have shown that including both genotypes that affect 5-HTT transcription (i.e., 5-HTTLPR and rs25531) may help to analyze the association of 5-HTT function and liability for different psychiatric disorders more adequately.…”
Section: Introductionmentioning
confidence: 99%